2019
DOI: 10.1139/cjfr-2018-0288
|View full text |Cite
|
Sign up to set email alerts
|

Understory vascular plant responses to retention harvesting with and without prescribed fire

Abstract: Wildfire is the predominant natural disturbance in the boreal forests of western Canada. Natural disturbance based forest management involves the use of retention harvesting to retain stand structural diversity after harvest; however, unlike fire, this partial harvesting technique does not cause combustion of the forest floor. Application of prescribed burning to areas treated with retention harvesting might emulate the influence of wildfires more effectively than harvesting alone. We compared understory vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Combined effects of fire and selective cutting on vegetation were also minor in Sudanese savanna woodlands [55] and for eucalypt forests in southern Australia [15]. However, stronger interactive effects of fire and timber harvesting have been reported elsewhere e.g., [14,56,57]. Barefoot et al [56] reported that overstorey thinning coupled with prescribed fire resulted in increases in ground flora richness, diversity and cover in mixed Pinus-hardwood stands in Alabama, USA.…”
Section: Discussionmentioning
confidence: 93%
“…Combined effects of fire and selective cutting on vegetation were also minor in Sudanese savanna woodlands [55] and for eucalypt forests in southern Australia [15]. However, stronger interactive effects of fire and timber harvesting have been reported elsewhere e.g., [14,56,57]. Barefoot et al [56] reported that overstorey thinning coupled with prescribed fire resulted in increases in ground flora richness, diversity and cover in mixed Pinus-hardwood stands in Alabama, USA.…”
Section: Discussionmentioning
confidence: 93%
“…Given the dominant understory species generally differ among ecoregions where brown bears inhabit (e.g. Hokkaido, Japan: dwarf bamboo (Hiura et al 1996), Alberta in Canada and Sweden: berries (Nilsson and Wardle 2005, Franklin et al 2019), Carpathian Mountain, Poland: ferns and berries (Ciarkowska and Miechówka 2019)), evaluation of the role of the understory in brown bear ecology and management should carefully consider regional differences. Additionally, understanding spatial patterns of habitat selection can assist prediction of bear–human conflict (Northrup et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Besides tree‐level attributes, the positioning of retention trees plays a crucial role in the effectiveness of retention trees, both within a stand (e.g. grouped vs. single tree retention and vicinity to intact stands, Franklin et al, 2019; Gibbons et al, 2008) and in the wider landscape (Mori et al, 2017; Vandekerkhove et al, 2013).…”
Section: Introductionmentioning
confidence: 99%